2022
DOI: 10.3390/ijms231911281
|View full text |Cite
|
Sign up to set email alerts
|

Role of Essential Amino Acids in Age-Induced Bone Loss

Abstract: Age-induced osteoporosis is a global problem. Essential amino acids (EAAs) work as an energy source and a molecular pathway modulator in bone, but their functions have not been systematically reviewed in aging bone. This study aimed to discuss the contribution of EAAs on aging bone from in vitro, in vivo, and human investigations. In aged people with osteoporosis, serum EAAs were detected changing up and down, without a well-established conclusion. The supply of EAAs in aged people either rescued or did not af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Specific AAs may preferentially bind to a calcium-sensing receptor, modulate its activation by calcium ions, and thus potentially impact bone turnover. Amino acids are also required for bone marrow stromal cells to promote differentiation into osteoblasts, synthesis of type I collagen, circulating levels of IGF-I and alkaline phosphatase [ 9 , 10 ]. Certain AA types, particularly amino acids from the aromatic group, can stimulate increases in intracellular calcium and ERK phosphorylation/activation and may impact an early stage of osteoclast differentiation by suppressing the attachment of osteoclasts and the resorption process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific AAs may preferentially bind to a calcium-sensing receptor, modulate its activation by calcium ions, and thus potentially impact bone turnover. Amino acids are also required for bone marrow stromal cells to promote differentiation into osteoblasts, synthesis of type I collagen, circulating levels of IGF-I and alkaline phosphatase [ 9 , 10 ]. Certain AA types, particularly amino acids from the aromatic group, can stimulate increases in intracellular calcium and ERK phosphorylation/activation and may impact an early stage of osteoclast differentiation by suppressing the attachment of osteoclasts and the resorption process.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data demonstrated that AAs should also be viewed as specific and selective signaling molecules in bone cells [ 7 , 8 ]. Bone mass can be elevated by amino acid-induced increases in calcium absorption efficiency, osteoblast proliferation and bone mineralization, synthesis of type I collagen, circulating levels of insulin-like growth factor-I (IGF-I) and alkaline phosphatase, suppressed osteoclast differentiation and reduced bone resorption [ 9 , 10 ]. Certain AA types, particularly amino acids from the aromatic group (phenylalanine, tryptophan, tyrosine) can stimulate an increase in intracellular calcium and extracellular signal-regulated kinase (ERK) phosphorylation/activation [ 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…54 For example, threonine can increase osteoblast proliferation and differentiation with decreasing osteoclast activity. 55 Moreover, the presence of nucleotides in the extracellular microenvironment is largely determined by their release from cells and regulates the function of osteoblasts. 56,57 Nucleotides like inosine promote osteoblast proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In order to differentiate into fully functional osteoblasts, naive cells in the bone require high amounts of amino acids 54 . For example, threonine can increase osteoblast proliferation and differentiation with decreasing osteoclast activity 55 . Moreover, the presence of nucleotides in the extracellular microenvironment is largely determined by their release from cells and regulates the function of osteoblasts 56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…I,J) Enriched KEGG pathways of metabolome response to PAC/GelMA, PDAC/GelMA, and PDMAPS/GelMA on I) day 3 and J) 7. formation. [65] Arachidonic acid, prostaglandin h2, and dinoprostone are classic markers for inflammation, which downregulated bone mineral content. [66] Bile acids, short-chain fatty acids, and trimethylamine N-oxide are the common substances in high-fat diet (HFD)-induced chronic diseases.…”
Section: Zwitterionic-ecm-regulated Osteogenic Metabolism Poolsmentioning
confidence: 99%